O projeto HBM4EU - exemplo de biomonitorização da exposição ocupacional ao crómio - Tavares, Ana Maria (2021)
Aula 5: O projeto HBM4EU - exemplo de biomonitorização da exposição ocupacional ao crómio. Projeto HBM4EU - General objective: To understand human exposure to chemicals and resulting health impacts and communicate with policy makers to ensure that the results are exploited in the design of new chemicals policies and the evaluation of existing measures.